2020
DOI: 10.1186/s12916-020-01814-4
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of methylprednisolone in hepatitis B virus-related acute-on-chronic liver failure: a prospective multi-center clinical trial

Abstract: Background Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is a severe condition with high mortality due to lack of efficient therapy. Until now, the use of methylprednisolone (MP) in HBV-ACLF is still controversial. We aimed to evaluate the efficacy and safety of MP in HBV-ACLF. Methods Totally 171 HBV-ACLF patients from three medical centers were randomly allocated into MP group (83 patients treated with MP intravenously guttae for 7 days plus standard treatment: 1.5 mg/kg/day [day 1–3],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…NACSELD definition also agreed that with high shortterm mortality in these patients in the absence of the proper management of underlying liver disease, liver support, and liver transplantation (4) studies are focusing on the further validation of the current definition of ACLF. Management of the underlying cause of CLD with suitable therapies, including antivirals for hepatitis B (HBV)-and hepatitis C virus (HCV)related liver disease, alcohol abstinence in alcoholic liver disease (ALD), and immunosuppressive therapies in autoimmune liver disease may avoid or reverse the development of cirrhosis (5)(6)(7). Contrarily, if the underlying cause is left untreated or it persists in patients with compensated cirrhosis, extended hepatic necrosis can destroy hepatic architecture, increase intrahepatic resistance, portal hypertension, damage liver parenchymal cells, and subsequently cause acute decompensation of the disease (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…NACSELD definition also agreed that with high shortterm mortality in these patients in the absence of the proper management of underlying liver disease, liver support, and liver transplantation (4) studies are focusing on the further validation of the current definition of ACLF. Management of the underlying cause of CLD with suitable therapies, including antivirals for hepatitis B (HBV)-and hepatitis C virus (HCV)related liver disease, alcohol abstinence in alcoholic liver disease (ALD), and immunosuppressive therapies in autoimmune liver disease may avoid or reverse the development of cirrhosis (5)(6)(7). Contrarily, if the underlying cause is left untreated or it persists in patients with compensated cirrhosis, extended hepatic necrosis can destroy hepatic architecture, increase intrahepatic resistance, portal hypertension, damage liver parenchymal cells, and subsequently cause acute decompensation of the disease (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that GC treatment improve the survival rate of the patients with HBV-ACLF. A prospective multi-center clinical trial totally included 171 HBV-ACLF patients, 83 patients treated with methylprednisolone [1.5 mg/kg/day (day 1-3), 1 mg/kg/day (day 4-5), and 0.5 mg/kg/day (day 6-7)] for 7 days, the results showed methylprednisolone treatment can increase the 6-month survival rate of HBV-ACLF patients ( 27 ). And there is a retrospective study included 349 patients with HBV-ACLF in 2021.…”
Section: Gc Therapy In Different Etiology Of Liver Failurementioning
confidence: 99%
“…The authors found MAPT to be superior to the CLF-C-ACLF, MELD and Child-Turcotte-Pugh scores in predicting 90-day mortality, with an area under the receiver operating characteristic curve of 0.802 with sensitivity of 71.77%, and specificity of 75.82% [ 195 ]. Recent high-quality studies have shown that TDF was superior to entecavir in HBV-ACLF (white blood cell count and HBV DNA reduction at two weeks independently predicted mortality at three months); ALSS treatment improved short-term survival and was associated with lower short-term death in patients with HBV-ACLF class 2; corticosteroid treatment did not improve transplant-free survival in patients with HBV-ACLF but, a metanalysis showed that it was effective in reducing jaundice, in-hospital mortality and ascites events; while a prospective multi-center clinical trial showed methylprednisolone therapy (1.5mg/kg/d day 1-3; 1 mg/kg/d day 4-5; and 0.5mg/kg/d day 6-7) increased six-month survival [ 196 - 200 ]. To summarize, specific mutations in HBV predispose to reactivation of the virus leading to ACLF in patients with HBV-related ACLF, which is also governed by HLA susceptibility and virus genotype in certain patient populations.…”
Section: Reviewmentioning
confidence: 99%